FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI DAN PENDAPATAN INDUSTRI PAKAIAN JADI DI KECAMATAN KEDIRI KABUPATEN TABANAN - Adiwinanta, I Made Dede; Martini Dewi, Ni Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 3 (2023): Vol.12.3. MARET 2023[166-230], 2023)
Small industry is a major component of local economic development in a village. Small industry is the sector that is easiest for the workforce to enter, because it does not require special requirements for admission to work such as higher education. One type of business in the manufacturing sector is the apparel industry. The development of this industry in Tabanan Regency is experiencing instability. This research was conducted in Kediri District, Tabanan Regency. This research is an associative quantitative research. The samples in this study were 40 business units. Data collection methods used are observation, structured interviews and in-depth interviews. The data analysis technique used in this research is path analysis. The results of the study show that 1) Capital, labor, technology and raw materials have a significant effect on the production of the apparel industry in Kediri District; 2) Capital, labor, technology, raw materials and production have a significant effect on the income of the apparel industry in Kediri District; and 3) Capital, labor, technology, and raw materials indirectly influence income through the production of the apparel industry in Kediri District keyword : Capital, labor, technology, raw materials, production, income